Peningkatan Kesehatan Ibu Dan Anak Melalui Penyuluhan Kebidanan Di Lapangan Orbit Perumnas Antang Blok 1 - April Artinanda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Maternal and child health is one of the key indicators in determining the overall health status of a community. High maternal and infant mortality rates are often caused by a lack of knowledge among mothers regarding reproductive health, pregnancy, childbirth, and newborn care. Therefore, a community service activity in the form of midwifery counseling was carried out at Lapangan Orbit Perumnas Antang Blok 1, aiming to improve maternal knowledge on maternal and child health. The methods used included lectures, interactive discussions, and simple demonstrations related to pregnancy care and newborn care. The results of the activity showed an increase in participants’ understanding of the importance of regular antenatal care, balanced nutrition, danger signs during pregnancy, and basic newborn care. This program is expected to raise awareness among mothers on the importance of maternal and child health, thus reducing the risk of pregnancy complications and improving the quality of family life.